Study of the effect of the microstructure on the hot deformability of a duplex stainless steel - Iza-Mendia, A.; Piñol-Juez, A.; Gutiérrez, I. (Revista de Metalurgia, 1998)
The complexity of the hot deformation behaviour of the ferrite and austenite in a duplex structure is increased as compared with that of single phase ferritic or austenitic steels. Important factors are: the spatial phase distribution with respect to the direction of the imposed deformation, the codeformation of both phases having considerably different mechanical properties, and the nature of the interface between austenite and ferrite. In the present study, the influence of these factors on the crack formation during the hot deformation is analyzed.